Analisis Penyelesaian Complaint Handling pada Pelayanan Sistem Operasional di BSI KCP Cemara Asri - Puspita, Windy; Nurwani, Nurwani; Anggraini, Tuti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the resolution of complaint handling at BSI KCP Cemara Asri. This research uses a descriptive qualitative research method that uses primary data and secondary data as sources of research data. The subject of this research is customer service at BSI KCP Cemara Asri. And the data collection techniques used were interviews and literature studies. This research found that the completion of complaint handling at BSI KCP Cemara Asri was carried out by customer service using a complaint handling resolution mechanism, namely carrying out standard service initiation, listening to customer complaints, saying apologies, asking customers for the chronology of complaints that occurred, verifying customer data, provide solutions to customers, ask customers to fill out a complaint form, and finally carry out standard service terminations. In completing complaint handling at BSI KCP Cemara Asri, there are supporting and inhibiting factors. So strategies need to be implemented to minimize the occurrence of customer complaints. So, to minimize the occurrence of customer complaints at BSI KCP Cemara Asri, what customer service must do in resolving complaint handling is to implement excellent service, namely providing information or explaining the products or services used by customers as well as explaining how to use the BSI Mobile application and Its function is so that later if a complaint occurs that is still relatively easy, the customer can resolve it themselves. So that it can minimize the occurrence of customer complaints in the future or similar complaints to these customers.